2010
DOI: 10.1007/s11120-010-9547-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthetic efficiency promotion of sugar beet (Beta vulgaris L.) by endophytic bacteria

Abstract: Very little is known about the physiological interactions between plants and endophytic bacteria. We investigated the impact of three endophytic bacteria, Bacillus pumilus 2-1, Chryseobacterium indologene 2-2, and Acinetobacter johnsonii 3-1, on the photosynthetic capacity and growth of sugar beet. Endophyte-free plants were obtained first and infected with the bacteria. Measurements of total chlorophyll content revealed very significant differences between endophyte-free beet plants and some infected by endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 39 publications
10
49
0
2
Order By: Relevance
“…As such reduction did not result in low soluble sugars content (Figure 2b), our data indicate the presence of other sugars derived from sucrose hydrolysis. In fact, Shi et al (2010) found higher fructose concentration in leaves of plants treated with endophytic bacteria. The inocula did not change Sta and NSC concentrations, regardless sugarcane genotype (Figures 2c, d).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…As such reduction did not result in low soluble sugars content (Figure 2b), our data indicate the presence of other sugars derived from sucrose hydrolysis. In fact, Shi et al (2010) found higher fructose concentration in leaves of plants treated with endophytic bacteria. The inocula did not change Sta and NSC concentrations, regardless sugarcane genotype (Figures 2c, d).…”
Section: Resultsmentioning
confidence: 91%
“…These changes suggest an improved absorption of light energy and use in photochemistry, a key physiological process responsible for ATP and NADPH production in chloroplasts. Shi et al (2010) also reported that bacteria inoculation caused an increase in ETR and improved photosynthesis, suggesting the presence of unknown compounds produced by bacteria that could increase ETR and chlorophyll metabolism. The presence of bacteria in leaves may also upregulate photosynthetic genes related to ferredoxin and NADPH ferredoxin (Bilgin et al 2010).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Shi et al [15] investigated the impact of three endophytic bacteria species, Bacillus pumilus, Chryseobacterium indologene, and Acinetobacter johnsonii, on the photosynthetic capacity of sugar beet (Betula vulgaris). The measurements of total chlorophyll content revealed very significant differences between non-inoculated beet plants and those inoculated with endophytic bacteria.…”
mentioning
confidence: 99%